Molecular characterization and antioxidant potential of Andean Chlorophytes from Ecuador - Juan Ortiz Tirado, Francisco Flores, Sebastián Maldonado, Raluka Mihae, Blanca Naranjo, Daysi Muñoz, Bangeppagari Manjunatha, Mariadoss Selvanayagam, Bugude Rajeswari (Journal of Applied Pharmaceutical Science, 2017)
Microalgae are an important bio resource for the productive matrix within the energy, agricultural and food sectors. In Ecuador, there are several studies on the use of native microalgae for bioremediation, food production and as alternative fuels. However, it is not common to identify this macrophyte at the species level, as well as the determination of nutritional and pharmaceutical properties. Classical identification of microalgae are based on their morphology and, in general, needs experienced taxonomists to achieve specific typifications. Molecular methods allow us to perform species-level identifications based on the amplification of multiple loci, where the sequences obtained can be compared to available public databases. Amplified DNA fragments show the presence of endemic species of nutraceutical interest and, together with chemical extraction processes, could provide reliable information for the use in the agricultural industry. Under this condition, the present research was carried out with endemic species of the genus Chlorella sp., belonging to the Cayambe Coca ecological reserve with antioxidant potential and for the use of environmental remediation as functional feed for livestock farms.
Keywords: Cayambe-Coca reserve, Chlorella sp, Nutraceutical properties.